Evaluación del aprovechamiento del rechazo de banano (Musa paradisiaca) para la obtención de una bebida alcohólica tipo vodka - Oña Cundulle, Tania Fernanda (2020)
This research work was carried out at the State Technical University of Quevedo and aimed to carry out the evaluation of the use of banana rejection (musa paradisiaca) with the addition of potato starch to obtain a vodka alcoholic beverage. 6 treatments and 4 repetitions were applied, a completely randomized design was made, with factorial arrangement. The treatments analyzed consisted of formulations with different percentages of banana, potato and water. The physicochemical and organoleptic characteristics were evaluated. The results of the research were satisfactory, of which the best treatment is T1 because of the organoleptic and physicochemical characteristics in which these stand out are its sensation of smell and taste of alcohol in addition to its astringency. Keywords: Physical-chemical analysis, potato starch, sensory evaluation, hydrolysis, Methanol.